(untitled) (Scientific journal of the Fergana State University, 2024)
In world linguistics, a number of studies have been conducted on semantically substantiating the meaning side of language units, developing their linguistic regularities, and determining their linguopoetic possibilities. The problem of learning antonyms within the framework of morphemic, lexical and grammatical units and on the basis of linguistic research methods was set. Indeed, defining the general and specific aspects of linguistic units, which differ according to the relation of form and meaning, is important to determine semantically opposite themes. The article discusses the relation of opposition, and this phenomenon is defined at the syntactic level within the context of conjunctions without a conjunction expressing the content of the contradiction.